Diseño de sistema de extracción de vapores derivados de la Nafta en operación de cargue para transporte terrestre Ecopetrol Bascula, Apiay (2021)
The current facilities of the naphtha loading dock located in the Apiay area, owned by ECOPETROL SA, have a deficient management of harmful vapors as a result of the operation of filling tanks with the product naphtha; the vapors are harmful to the operating personnel and the community. These vapors contain benzene, which is used as an additive in gasoline to increase octane, prevent engine knocking and for crude oil dilution; consequently, the vapors appear when the liquid level and internal pressure increase VOCs (Volatile Organic Compounds). VOCs include the most polluting component, benzene, which is highly toxic. It has been scientifically proven that when inhaled or in contact with the skin it has carcinogenic effects, such as: [4] myelogenous leukemia, lymphocytic leukemia, non-Hodgkin's lymphoma. Multiple Myeloma. Lung cancer, kidney cancer,